Le rapport Fisher, un an après - Moreau, Rémi (Assurances, 1981)
Lloyd's London has appointed a special committee to enquire into the organization and certain methods followed by their underwriting syndicates. A report has been issued which is known as "The Fisher Working Party on Self Regulation." Mr. Rémi Moreau has analyzed briefty its contents under the title of "The Fisher Report, one year later."